Peripheral Retinal Diseases: Indications for Prophylactic Laser Treatment Versus Observation (Canadian Eye Care Today, 2024)
Peripheral retinal diseases encompass a diverse group of conditions that can impact visual health and function. While some of these conditions are asymptomatic and may have a benign course, others can progress to potentially sight-threatening complications, such as retinal detachment, especially in the context of visual symptoms. Careful clinical evaluation and timely intervention are essential in managing peripheral retinal diseases to prevent loss of visual acuity, particularly when predisposing risk factors are present. Obtaining a proper history may help identify some genetic conditions associated with higher incidence of retinal tears and detachment such as high myopia or Stickler syndrome. Other factors to consider include the new onset of symptoms of posterior vitreous detachment, prior history of trauma or relatively recent intraocular surgery such as cataract surgery, intravitreal injection or YAG capsulotomy.